Tests Research on Grouting Materials of Waste-Concrete-Powder Cement for Goaf Ground Improvement - Zhilin Dun; Mengqi Wang; Lianwei Ren; Zhiyuan Dun (Advances in Materials Science and Engineering)
Waste concrete powder (WCP) is proposed to replace part of the cement to seek environmentally friendly grouting materials for ground improvement in mine goaf. The optimal mixing proportion was selected based on the performance indexes of the water-separation ratio, stone rate, viscosity, setting time, and compressive strength. X-ray diffraction (XRD) and scanning electron microscopy (SEM) tests were also conducted to analyze mineralogical phases and investigate the microscopic mechanism. Test results show that the slurry prepared by the substitution rate of 70% and adding 0.05% water-reducing agent meets well the requirements of ground grouting in mine goaf. The WCP produced by grinding mainly exerts microaggregate effect in the slurry due to low activity. A lot of pores on the surface of WCP were shown by SEM which can absorb the water in the slurry and increase the stone rate. The WCP application for ground grouting in mine goaf can not only recycle WC but also provide new grouting materials for goaf ground.